Development of optical coherence tomography incorporated image processing algorithms for the multidimensional assessment of concealed enamel micro-crack - Abu Saleah, Sm; Cho, Hoseong; Amrin Luna, Jannat; Seong, Daewoon; Eranga Wijesinghe, Ruchire; Han, Sangyeob; Kim, Shinheon; Jeon, Mansik; Kim, Jeehyun (Infrared physics & technology, 2024)
•A developed surface noise removal algorithm can be useful for better visualization.•Concealed enamel micro-cracks (EMCs) were detected using OCT image thresholding.•Micro-meter range progressions of EMCs (due to orthodontic treatment) were detected.•Multi-dimensional assessments of EMCs were performed using developed algorithms.•Developed algorithms can be useful in monitoring EMCs to avoid further damage. Enamel microcracks (EMCs) are tiny fractures that occur in the outer layer of teeth, allowing some extrinsic stains and leading to an unaesthetic tooth. Additionally, the EMCs enhance the accumulation of plaque and thus EMCs could be highly suspectable zones for caries development. Therefore, the assessment of EMCs is crucial for early diagnosis and to prevent unwanted damage to teeth. In this study, a concealed EMCs detection and length-measuring algorithm, and an EMCs width-measuring algorithm were applied for optical coherence tomography (OCT) image analysis to assess the EMCs progression in both length and width. Additionally, a surface noise-removing algorithm was developed to obtain a better visualization of OCT cross-sectional and volumetric images. The developed algorithms were successfully used to detect concealed EMCs and track their progression in both length and width directions before and after the orthodontic treatment. Obtained results revealed a micro-scale progression of EMCs in both length and width directions after the orthodontic treatment, where the averaged progression of EMCs in length and width were 712.5 and 92.75 µm, respectively. Therefore, high-resolution, non-invasive OCT imaging with developed image processing algorithms can be a fruitful solution to use as a diagnostic tool to monitor the precise coordinates of concealed EMCs throughout the orthodontic treatment.